Policy can be seen (the materials of the Second Perm Forum «Visualization of the choice: political agitation as science and art») - Kovin, V.S.; Petrova, R.I.; Filippova, E.Yu. (Perm Federal Research Centre Journal, 2018)
The article describes the Second Perm Forum «Visualization of choice: political agitation as a science and art» which was held in Perm from May 15 to June 5, 2018 and initiated by the Department for the Study of Political Institutions and Processes of the PFRC of the Ural Branch of the Russian Academy of Sciences. The authors report on areas that took place in the framework of the forum, and draw conclusions about the prospects of studying methods and visualization mechanisms and representation of political.